2022
DOI: 10.1155/2022/3097521
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] A Novel Protein Elicitor (PELL1) Extracted from Lecanicillium lecanii Induced Resistance against Bemisia tabaci (Hemiptera: Aleyrodidae) in Gossypium hirsutum L

Abstract: Protein elicitors play a key role in signaling or displaying plant defense mechanism and emerging as vital tools for biocontrol of insects. This study was aimed at the characterization of the novel protein elicitor isolated from entomopathogenic fungi Lecanicillium lecanii (V3) strain and its activity against whitefly, Bemisia tabaci, in cotton (Gossypium hirsutum L.). The sequence of purified elicitor protein showed 100% similarity with hypothetical protein LEL_00878 (Cordyceps confragosa RCEF 1005) (GenBank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
2
2
0
Order By: Relevance
“…showed induced systemic resistance and upregulation of plant defense pathways associated genes in tomato plants against green peach aphid ( M. persicae ) by the exogenous foliar application of elicitor proteins derived from a necrotrophic fungus Botrytis cinerea , from an entomopathogenic fungus Lecanicillium lecanii and from a gram‐positive bacteria Bacillus amyloliquefaciens , respectively. Similarly, significant suppression of fecundity and survival of whitefly ( Bemisia tabaci ) concomitantly with the upregulation of plant defense genes have been shown by the application of partially purified proteins extracted from L. lecanii and B. bassiana 17,40,41 . Results of our study also corroborate the findings of Nam et al 42 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…showed induced systemic resistance and upregulation of plant defense pathways associated genes in tomato plants against green peach aphid ( M. persicae ) by the exogenous foliar application of elicitor proteins derived from a necrotrophic fungus Botrytis cinerea , from an entomopathogenic fungus Lecanicillium lecanii and from a gram‐positive bacteria Bacillus amyloliquefaciens , respectively. Similarly, significant suppression of fecundity and survival of whitefly ( Bemisia tabaci ) concomitantly with the upregulation of plant defense genes have been shown by the application of partially purified proteins extracted from L. lecanii and B. bassiana 17,40,41 . Results of our study also corroborate the findings of Nam et al 42 .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, significant suppression of fecundity and survival of whitefly (Bemisia tabaci) concomitantly with the upregulation of plant defense genes have been shown by the application of partially purified proteins extracted from L. lecanii and B. bassiana. 17,40,41 Results of our study also corroborate the findings of Nam et al 42 and Javed et al 43 demonstrating the significant suppressive effects of an elicitor protein PeVL1 extracted from entomopathogenic fungus Verticillium lecanii on the development, survival and growth parameters of bean aphid M. japonica in bean plants and of rice leaf folder Marasmia ruralis in rice plants, respectively. Application of this elicitor protein induced systemic resistance against the larvae by activating plant defense pathways including JA, SA and ET.…”
Section: Discussionsupporting
confidence: 90%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%